Design and Analysis of a Wheel-legged Obstacle Climbing Robot - Yang Fan; Wu Heli; Luo Chenhui (Jixie chuandong)
Aiming at the wheel-legged type obstacle robot,a novel metamorphic wheel for wheel-legged obstacle climbing robot（ WOCR） is designed to make the robot to switch between wheels and legs. Firstly,the working principle of the metamorphic wheel is introduced and the three dimension model is established in Pro/E. Secondly,the deploy angle range of the wheel is analyzed in theory. The kinematic simulation for the deploy progress is carried out in ADAMS to verify the theoretical analysis result. The simulation result is similar to the theoretical result,which indicates the wheel structure is viability. At last,the obstacle climbing performance of the wheel is analyzed and the result shows the height of obstacle climbing after deploying the wheel is 2. 2 times than that before deploying and succeed in climbing a 200 mm high step. These indicate that the wheel possessed high capacity of obstacle climbing and can be applied in WOCR.